The Influence Of Sales Promotion, Hedonic Shopping Motivation, And Shopping Lifestyle On Impulse Buying In E-Commerce Shopee - Nisak, Aviathun; Kusumaningtyas, Dian (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : The aim of this research is to analyze whether there is a significant influence between sales promotion variables, hedonic shopping motivation, and shopping lifestyle both partially and simultaneously on impulsive purchases on Shopee e-commerce at University of Nusantara PGRI Kediri. Design/Methode/Approach : This research uses a quantitative approach with a type of causal research. The population of this research is all University of Nusantara PGRI Kediri students who have made online purchases via the Shopee application. The sampling technique uses incidental sampling with the Lemeshow formula which is known to be 100 respondents. This research uses descriptive statistical data analysis techniques, classical assumption tests, multiple linear regression, coefficient of determination, and hypothesis testing with SPSSv23. Research Finding : The results of the research show that the variables (1) sales promotion, hedonic shopping motivation, and shopping lifestyle have an effect both partially and simultaneously on impulse buying, (2) the sales promotion variable has a non-positive effect on impulse buying, and (3) hedonic shopping motivation and Shopping lifestyle has a positive effect on impulse buying on Shopee e-commerce at University of Nusantara PGRI Kediri